Facial nerve decompression via posterior tympanotomy approach in traumatic facial nerve palsy - Prabir Paul; Sabagirish K; B Choudhury; K Upadhyay; S Raina (The Indian Journal of Neurotrauma, 2010)
We managed two cases of facial palsy following trauma, who were decompressed via posterior tympanotomy approach. Both cases improved following surgery. Investigations, surgery and post op management are discussed. We conclude that posterior tympanotomy approach can be used for facial nerve decompression till first genu.